Anxiety and depression among Chinese children with and without reading disabilities. (12th July 2021) - Wang, Li‐Chih
Abstract : This study aims to compare anxiety and depression among male and female Chinese children with and without reading disabilities (RDs) and to examine the diverse impacts of anxiety and depression on children's reading comprehension. A total of 132 Chinese children from third to sixth grade living in Taiwan were recruited; half had RD, and the other half were typically developing children. Our results from the first analysis revealed that the anxiety level of female children with RD was significantly higher than that of the other three groups of participants, while the depression level of typically developing children was significantly lower than that of children with RD in general. Additionally, our results regarding the predictive abilities of gender and anxiety for reading comprehension as well as the moderating effect of gender on the ability of anxiety to predict reading comprehension were all statistically significant for the typically developing group but not the RD group. These differences between these two groups were further confirmed by multi‐group analysis. Our results enhance the existing knowledge on Chinese children with RD and can increase practitioners' awareness of the possibility of higher levels of anxious and depressive symptoms among these children.